IMAGE-TEXT RELATION INTERPRETATION: TEACHERS’ VISUAL-VERBAL COMPETENCE IN TEACHING TEXTS - Yustika Nur Fajriah; Fuad Abdul Hamied; Wawan Gunawan (LPMPP Universitas Negeri Yogyakarta, 2021)
Multimodal literacy instruction is such a new shift of the literacy in which the construction of knowledge is led to be more socially and contextually bounded. Due to the urgency that teachers have to own multimodal competencies, this study aimed to investigate EFL teachers’ competence in interpreting visual-verbal relations to teach multimodal texts. To collect the data, an online test through the Google form platform was distributed. As many as 43 responses were collected from junior and senior high school teachers in one of the cities in Indonesia. A semi-structured interview was also conducted with six purposive participants. The data in this research were then analysed based on Royce’s criteria of image-text relation. The analysis found that the teachers only partially possessed multimodal competencies. It means that that they had used images to help them teach the texts but had insufficient knowledge on how to utilize the images as meaning-making sources. Then, based on the finding, it is suggested that the teachers should improve their competences in interpreting multimodal meanings in texts, so images are used not only for making learning materials interesting but also for making more meanings from the texts.